Study of different performance measures and their relations in satellite‐based and terrestrial quantum communication - Avik Mukhopadhyay; Shantom Kumar Borah; Yashkalp Sharma; Sainath Bitragunta; Vinay Chamola (IET Quantum Communication, 2021)
Abstract Rapid developments in quantum communication are paving the way forward for more advanced technologies. Conventional channels like optical fibres have been a great resource in recent decades. However, they suffer largely from exponential transmissivity decays and are not suitable for very long‐distance communication. Satellite links along with quantum cryptography can be the foundation of modern quantum communication systems. This work presents an overview of the hybrid quantum repeater with a detailed analysis of different parametric relations in satellite‐based communication from experimental data. The link efficiency between the satellite‐based scheme and terrestrial scheme is also compared, emphasising the satellite‐based scheme's importance for quantum communication. Finally, we present a performance analysis of different quantities and derive relations between them.